Dominasi Etnis Minangkabau di Muara Bungo - Rahman, Arif; Hardi, Etmi (Jurusan Sejarah FIS UNP, 2024)
The aim to be achieved in this research is to analyze in depth the Minangkabau ethics that dominate the Bungo market. The method used in this research is a literature study where researchers use secondary data obtained from various related articles and books that are relevant to the research being studied. The results of this research show that: They have trust in which there are social relationships that are based on feelings. Furthermore, it is related to their social network where they have the ability to form a good social network by involving various social relationship networks. Furthermore, reciprocity emphasizes the mechanism of exchange of kindness that is directed towards a group of individuals. There are social norms that are upheld by the Minangkabau ethnic group in the trade process. This mechanism emphasizes good behavior that exists in the social order in the market area.